"I Just Didn't Want to Risk It": How Perceptions of Risk Motivate Charter School Choice Among Latinx Parents. (August 2022) - Szabo, Julia
Latinx students now make up the largest share of charter school students nationally. In this article, I focus on Latinx charter school choosers in Houston, Texas, and ask what motivates Latinx parents to exit district schools. Drawing on interviews with 31 families, I find that perceptions of present and future risk motivate charter school choice. Perceptions of present risk centered on children's negative experiences with safety and academics and parents' negative experiences when they attempted to intervene in district schools. Perceptions of future risk focused on future district schools and relied on information from networks, observations, and the educational experiences of U.S.-born parents. Parents framed charter school choice as a strategy to mitigate risk and protect their children's educational futures.